Han Feizi's Political Philosophy and Today's China - Kusumohamidjojo, Budiono (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
Han Feizi is a Chinese thinker who lived in the 3rd century BCEand had the opportunity to inspire the Emperor Qin Shi Huangdiwho is acknowledged as the founder of the Empire of China.Taking the path of his realist Confucian teacher Xunzi (contrary toMengzi who was an idealist Confucian), he believed in the evilcharacter of the human being, as basically everyone only prioritizesits own needs. Therefore Han Feizi deems it most important thatthe ruler establishes order and peace in society. As such Han Feiziteaches a political theory that differs from the mainstream of theother classical Chinese thinkers in general who consider socialethics as most significant. To establish harmony in society, he findsstrict laws, shrewd statecraft and clear authority more decisive thanthe personal moral virtues of the ruler as taught by Confucius. Inorder to govern effectively and efficiently, the ruler should employthe “two handles” of governing by punishing law breakers andrewarding law abiders proportionally vis-à-vis all his subjects. Itwas indeed that kind of governance that was pursued by MaoZedong while dealing with the officials of the Communist Party ofChina, resembling that what the Government of China did to dealwith civil unrest in Tibet in the 1950s and 2008, and now in Urumqias well.